INTERNATIONAL MANAGEMENT INTRODUCTION - Bolbekova Ug'iloy Jaloliddinovna; Rajabov Ma’ruf Normurodovich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This article explores the concept of International Management and its growing importance in today’s globalized economy. International management refers to the process of planning, organizing, leading, and controlling business operations across national borders. The study highlights key aspects such as cultural diversity, global leadership, international strategy, and cross-border communication. It also examines the challenges faced by managers in multinational environments, including differences in legal systems, economic conditions, and cultural values.